Strategi Pemasaran dalam Meningkatkan Penjualan Cassava Snacks - Nadia Ekalaya Ekalaya; Sabinus Beni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out the marketing mix strategy of the Cassava Snack cassava chips business using social media, namely by using Facebook, Whatsapp and marketing directly to consumers. The 4P marketing mix in this study is products, prices, promotions, and places. The methods used in this study are qualitative methods and descriptive approaches. To obtain data in this study, researchers conducted observations, direct interviews, and documentation. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of this study show that the marketing mix strategy using the 4P method can increase product sales if applied properly, besides that marketing using social media can also help increase product sales, besides that product quality can also affect the marketing mix, because consumers will certainly see the product first from the quality, therefore quality plays a very important role in the marketing mix of a product especially in Cassava Snack products